Colloidal assembly manipulated by light-responsive Ag3PO4 nanoparticles. Issue 80 (16th September 2021) - Xu, Fei; Zhu, Jiao; Wang, Huaguang; Zhang, Zexin
Abstract : PS colloids assemble into crystallites, chains and gels manipulated by light-responsive Ag3 PO4 nanoparticles. Abstract : We report controllable assembly of polystyrene (PS) microspheres via a photocatalytically driven electroosmotic flow deriving from UV irradiation of Ag3 PO4 nanoparticles in water. A series of assembly phases, including crystallites, chains and gels, are programmed by systematically modulating the UV intensity, the packing density of the PS microspheres and the concentration of the Ag3 PO4 nanoparticles. Our findings demonstrate an important ability of light-responsive nanoparticles for colloidal assembly, which offers a new pathway toward effective manipulation of assembly at the microscale.